An assessment of weight change associated with the initiation of a protease or integrase strand transfer inhibitor in patients with human immunodeficiency virus. (2nd August 2020) - Chow, Wing; Donga, Prina; Côté-Sergent, Aurélie; Rossi, Carmine; Lefebvre, Patrick; Lafeuille, Marie-Hélène; Emond, Bruno; Hardy, Hélène
Abstract: Objective: Evidence suggests that integrase strand transfer inhibitors (INSTIs) are associated with greater weight gain than other antiretrovirals. This real-world study compares weight/body mass index (BMI) change between insured US patients with human immunodeficiency virus (HIV-1) initiating a protease inhibitor (PI) or INSTI. Methods: A retrospective longitudinal study was conducted using Decision Resources Group's Real World Data Repository (7/17/2017-6/1/2019). Adult patients with HIV-1 who initiated a new PI or INSTI on or after 7/17/2018 (index date) and had ≥12 months of continuous pre-index clinical activity were included. Baseline characteristics were balanced using inverse probability of treatment weighting. The proportion of patients with ≥5% weight/BMI increases and mean weight/BMI change from pre- to post-index were compared using odds ratios (ORs) and mean differences (MDs). Results: 20, 367 patients (9993 PI, 10, 374 INSTI) were included (mean age = 50 years; ∼30% females). Pre- and post-index weight and BMI measurements were available in 429 and 430 PI patients, and 397 and 383 INSTI patients, respectively (mean time between index and post-index measurements: ∼7 months). The PI cohort was 39%/49% less likely to experience ≥5% weight/BMI increase than the INSTI cohort, respectively (OR [≥5% weight gain] = 0.61; p = .014; OR [≥5% BMI gain] = 0.51; p < .001). Mean weight/BMI gain was significantly lower in the PI cohort than the INSTI cohort (weight MD = –1.90 kg [–4.19 lbs], BMI MD = –0.61kg/m 2 ; both p < .001). Conclusions: Relative to INSTI, patients initiating a new PI were less likely to experience ≥5% weight/BMI gain post-index. Additionally, mean weight/BMI gain was lower in the PI than in the INSTI cohort.